Text in 3D: Some Legibility Results - Larson, Kevin; Dantzich, Maarten van; Czerwinski, Mary; Robertson, George (2000)
3D user interfaces for productivity applications often display object labels or whole documents in arrangements where the text is rotated instead of screen aligned. Rotating a document sideways saves screen real estate while allowing inspection of the document's content. This paper reports on an initial reading speed study of text rotated around a vertical axis and manipulated in size. We found that with sufficient rendering quality small text can be substantially rotated before reading performance suffers, and large text legibility is nearly unaffected by rotation. The empirically derived guidelines we present are the first published for 3D text and important for the design of 3D information visualizations.
Extended Abstracts of CHI '2000, Human Factors in Computing Systems